Cost-Effectiveness of the Chronic Disease Self-Management Program: Implications for Community-Based Organizations - Basu, Rashmita; Ory, Marcia G.; Towne, Samuel D.; Smith, Matthew Lee; Hochhalter, Angela K.; Ahn, SangNam (Frontiers in Public Health, 2015)
.